Hidden on the high wire - Kacer, Kathy, 1954- (Holocaust remembrance book for young readers., 2022)
Irene travels around Germany performing with her family's circus, but Hitler's rise to power soon puts her Jewish family in grave danger. When the circus is forced to close down and Irene's father is taken away, she and her mother go into hiding with another circus where Irene returns to the high wire, and her mother joins other seamstresses making costumes for the performers.